A Pedagogical Approach for Modeling and Simulation of Switching Mode DC-DC Converters for Power Electronics Course - Han Yang (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
The power electronics course is a rather challenging subject for instructors and undergraduate students pursuing Bachelor’s Degree in Electrical Engineering. To enhance teaching effectiveness and motivate self-learning capabilities of the students, this paper presents a pedagogical approach for mathematical modeling and simulation of switching mode DC-DC converters. The Buck and Boost converters are analyzed as benchmark systems to study the power converter modeling methodologies. And a comparative analysis using digital simulation from Matlab/Simulink and ATP/EMTP is presented. A summary of student survey is also presented, which shows a high level of satisfaction. The presented pedagogical approach would be useful for classroom teaching for the power electronics course and similar engineering courses.DOI:http://dx.doi.org/10.11591/telkomnika.v10i6.1361